THE AUTHORSHIP OF THE SEX HYMNI ATTRIBUTED TO ST. JOHN OF DAMASCUS - Hussey, J. M. (The journal of theological studies, 1946)
J. M. HUSSEY; THE AUTHORSHIP OF THE SEX HYMNI ATTRIBUTED TO ST. JOHN OF DAMASCUS, The Journal of Theological Studies, Volume os-XLVII, Issue 187-188, 1 October